2014
DOI: 10.3384/diss.diva-106733
|View full text |Cite
|
Sign up to set email alerts
|

Doping of high-Al-content AlGaN grown by MOCVD

Abstract: The high-Al-content Al x Ga 1-x N, x > 0.70, is the principal wide-band-gap alloy system to enable the development of light-emitting diodes operating at the short wavelengths in the deep-ultraviolet, λ < 280 nm. The development of the deep-ultraviolet light-emitting diodes (DUV LEDs) is driven by the social and market impact expected from their implementation in portable units for water/surface disinfection and based on the damaging effect of the deep-ultraviolet radiation on the DNA of various microorganisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…The effective activation energy was determined to be 29 meV in Mg-doped AlxGa1-xN/AlN superlattices with an average Al composition of 0.62, and 18 meV with an average Al composition of Kakanakova-Georgieva et al estimated a hole concentration of~10 14 cm −3 for Mg-doped Al 0.85 Ga 0.15 N layers, from the a room temperature resistivity of 7 kΩ cm by assuming a hole mobility of 2 cm 2 V −1 s −1 , when grown using a hot wall MOCVD system which purportedly leads to growth conditions for reduced compensation by native defects [108]. The same authors also reported a resistivity of 2 kΩ cm and 60 Ω cm for Al 0.70 Ga 0.30 N and Al 0.60 Ga 0.40 N, respectively, by using the hot wall MOCVD reactor with optimized V/III ratio [109]. If the same hole mobility of 2 cm 2 V −1 s −1 is assumed, the hole concentrations in the Al 0.…”
Section: Doping Considerations In High Al-molar Fraction Alganmentioning
confidence: 67%
“…The effective activation energy was determined to be 29 meV in Mg-doped AlxGa1-xN/AlN superlattices with an average Al composition of 0.62, and 18 meV with an average Al composition of Kakanakova-Georgieva et al estimated a hole concentration of~10 14 cm −3 for Mg-doped Al 0.85 Ga 0.15 N layers, from the a room temperature resistivity of 7 kΩ cm by assuming a hole mobility of 2 cm 2 V −1 s −1 , when grown using a hot wall MOCVD system which purportedly leads to growth conditions for reduced compensation by native defects [108]. The same authors also reported a resistivity of 2 kΩ cm and 60 Ω cm for Al 0.70 Ga 0.30 N and Al 0.60 Ga 0.40 N, respectively, by using the hot wall MOCVD reactor with optimized V/III ratio [109]. If the same hole mobility of 2 cm 2 V −1 s −1 is assumed, the hole concentrations in the Al 0.…”
Section: Doping Considerations In High Al-molar Fraction Alganmentioning
confidence: 67%
“…[100] The same authors also reported a resistivity of 2 kΩ cm and 60 Ω cm for Al0.70Ga0.30N and Al0.60Ga0.40N, respectively, by using the hot wall MOCVD reactor with optimized V/III ratio. [101] If the same hole mobility of 2 cm 2 V -1 s -1 is assumed, the hole concentrations in the Al0.70Ga0.30N and Al0.60Ga0.40N layers are deduced to be ~3.5×10 14 cm -3 and ~1×10 16 cm -3 , respectively. Through the optimization of growth conditions, highly conductive p-type Mg-doped Al0.70Ga0.30N thin films were realized by employing a high V/III ratio and moderate Mg concentration by Kinoshita et al [102] Such conditions were found to effectively suppress self-compensation by the formation of nitrogen vacancy complexes, which are considered to be the compensating donors.…”
Section: Doping Considerations In High Al-molar Fraction Alganmentioning
confidence: 99%